Analyzing social networks - Borgatti, Stephen P.; Everett, Martin G. 1955-; Johnson, Jeffrey C. (Jeffrey Carl) (SAGE Publications, 2013)
"Written by a stellar team of experts, Analyzing Social Networks is a practical book on how to collect, visualize, analyze and interpret social network data with a particular emphasis on the use of the software tools UCINET and Netdraw. The book includes a clear and detailed introduction to the fundamental concepts of network analyses, including centrality, subgroups, equivalence and network structure, as well as cross-cutting chapters that helpfully show how to apply network concepts to different kinds of networks. Written using simple language and notation with few equations, this book masterfully covers the research process, including: The initial design stage - Data collection and manipulation - Measuring key variables - Exploration of structure - Hypothesis testing - Interpretation. This is an essential resource for students, researchers and practitioners across the social sciences who want to use network analysis as part of their research."--Publisher's website.